APLIKASI PEMANFAATAN TEKNOLOGI TEXT-TO-SPEECH DAN SPEECH-TO-TEXT SEBAGAI ASISTEN PENGEMUDI BERBASIS ANDROID - Indra Maulana Yusup Kusumah; Haris Irnawan; Teguh Dwi Fasya (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2015)
Along with the rapid development of information technology and the many new emerging technologiessuch as android, ios, etc. The emergence of new technologies that no other aims in order to support the needs ofthe majority community has a high mobility. By utilizing increasingly sophisticated information technology, allcommunity activities wherever and whenever they can be done quickly and easily.In this regard, here I will explain a software that can support the needs of a driver, by utilizing the TextTo Speech technology can be abbreviated TTS, the concentration of a driver will not be disturbed when there isan incoming message or phone. TTS is a system of hardware and software that has the ability to converthandwriting into words.Software development methodology uses waterfall method and system for using flowmap its design and UML.Therefore the preparation of this report aims to develop TTS technology as an assistant driver informationsystem and built with android-based technologies.Keywords: TTS, driver, UML, android.